From waste to fashion – a fashion upcycling contest - Marques, António Dinis (2019)
Fashion industry has a huge environmental impact, with increasing consequences all around the world. It is clear that the fashion consumers and stakeholders need to evaluate present status quo, according principles of sustainability and circular economy. Circular economy can be a guideline for the fashion industry, promoting product development focused on sustainable products (e.g., green products and cleaner technologies) and recyclability (e.g., upcycling and reuse of fibers from disposal clothes). Textile wastes, including clothing (retail stocks or personal used items) and fabrics (knitting, woven or non-woven industrial products) from different sources, need to loose negative image achieving new consumers’ value and to become “raw materials” to close the loop. This paper aims to present and discuss the participation of two young fashion designers in Upcycling Project by TAP. Challenges and contests like this, coming from several sectors and different organizations, are important and highlight the urgency to change old ideas and concepts, increasing creativity and beauty, even if the fashion industry is not ready for it yet. Using old textiles from plane seats and metal accessories from seat belts as raw materials, the designers developed a conceptual long coat according fashion design principles and they managed to get the 3rd place among height final participants. The description of the different stages (initial drawing, materials selection, modelling, cutting, sewing and finishing) will be presented, as well as fashions’ process design (ecodesign and upcycling) focused in sustainable approaches and circularity. A main outcome of this contest was the media exposure obtained by the designers, including in the television (RTP1) and several websites. A more conscious fashion consumer needs information and knowledge about these topics to demand this conscience from the fashion brands.